Co-ordinated control of the Aurora B abscission checkpoint by PKCε complex assembly, midbody recruitment and retention. Issue 12 (25th June 2021) - Watson, Lisa; Soliman, Tanya N.; Davis, Khalil; Kelly, Joanna; Lockwood, Nicola; Yang, Xiaoping; Lynham, Steven; Scott, John D.; Crossland, Victoria; McDonald, Neil Q.; Mann, David J.; Armstrong, Alan; et al.
Abstract : A requirement for PKCε in exiting from the Aurora B dependent abscission checkpoint is associated with events at the midbody, however, the recruitment, retention and action of PKCε in this compartment are poorly understood. Here, the prerequisite for 14-3-3 complex assembly in this pathway is directly linked to the phosphorylation of Aurora B S227 at the midbody. However, while essential for PKCε control of Aurora B, 14-3-3 association is shown to be unnecessary for the activity-dependent enrichment of PKCε at the midbody. This localisation is demonstrated to be an autonomous property of the inactive PKCε D532N mutant, consistent with activity-dependent dissociation. The C1A and C1B domains are necessary for this localisation, while the C2 domain and inter-C1 domain (IC1D) are necessary for retention at the midbody. Furthermore, it is shown that while the IC1D mutant retains 14-3-3 complex proficiency, it does not support Aurora B phosphorylation, nor rescues division failure observed with knockdown of endogenous PKCε. It is concluded that the concerted action of multiple independent events facilitates PKCε phosphorylation of Aurora B at the midbody to control exit from the abscission checkpoint.